Fluorogen Activating Protein–Affibody Probes: Modular, No-Wash Measurement of Epidermal Growth Factor Receptors - Wang, Yi (Bioconjug Chem, 2014)
[Image: see text] Fluorescence is essential for dynamic live cell imaging, and affinity reagents are required for quantification of endogenous proteins. Various fluorescent dyes can report on different aspects of biological trafficking, but must be independently conjugated to affinity reagents and characterized for specific biological readouts. Here we present the characterization of a new modular platform for small anti-EGFR affinity probes for studying rapid changes in receptor pools. A protein domain (FAP (dL5**)) that binds to malachite-green (MG) derivatives for fluorescence activation was expressed as a recombinant fusion to one or two copies of the compact EGFR binding affibody Z(EGFR:1907). This is a recombinant and fluorogenic labeling reagent for native EGFR molecules. In vitro fluorescence assays demonstrated that the binding of these dyes to the FAP–affibody fusions produced thousand-fold fluorescence enhancements, with high binding affinity and fast association rates. Flow cytometry assays and fluorescence microscopy demonstrated that these probes label endogenous EGFR on A431 cells without disruption of EGFR function, and low nanomolar surface K(d) values were observed with the double-Z(EGFR:1907) constructs. The application of light-harvesting fluorogens (dyedrons) significantly improved the detected fluorescence signal. Altering the order of addition of the ligand, probe, and dyes allowed differentiation between surface and endocytotic pools of receptors to reveal the rapid dynamics of endocytic trafficking. Therefore, FAP/affibody coupling provides a new approach to construct compact and modular affinity probes that label endogenous proteins on living cells and can be used for studying rapid changes in receptor pools involved in trafficking.